PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PENINGKATAN PROFESIONAL GURU TERHADAP KINERJA GURU DI MASA PANDEMI COVID-19 - Russamsi, Yunus; Hadian, Hanhan; Nurlaeli, Acep (Universitas Nurul Jadid, 2020)
Process during the Covid-19 pandemic which was carried out at home in accordance with a government circular in order to break the chain of the spread of Covid 19.